Attitudes toward advance directives and the impact of prognostic information on the preference for cardiopulmonary resuscitation in medical inpatients in Chiang Mai University Hospital, Thailand - Sittisombut S. (2014)
Our previous study revealed that cardiopulmonary resuscitation (CPR) was performed in 65.7% of 411 terminally ill patients who died in a tertiary-care university hospital in northern Thailand. Advance directives (ADs) are needed to ensure that life-sustaining therapies are used more appropriately. To investigate inpatients' attitudes regarding ADs for CPR and the impact of providing prognostic information on treatment preferences for CPR, we interviewed a randomly selected group of 200 ambulatory medical inpatients in multiple sessions. The results showed that most subjects had a positive attitude towards ADs for CPR. The majority preferred to have CPR when no information was provided on the chance of survival. However, this proportion decreased depending on the prognostic scenarios. Our investigation suggested that the preference of patients for CPR should be assessed individually and gradually, with adequate information given on the chance of survival. © 2005 Blackwell Publishing Asia Pty Ltd.